2012
DOI: 10.1037/a0027515
|View full text |Cite
|
Sign up to set email alerts
|

Peer network drinking predicts increased alcohol use from adolescence to early adulthood after controlling for genetic and shared environmental selection.

Abstract: Research consistently links adolescents' and young adults' drinking with their peers' alcohol intake. In interpreting this correlation, 2 essential questions are often overlooked. First, which peers are more important, best friends or broader social networks? Second, do peers cause increased drinking, or do young people select friends whose drinking habits match their own? The present study combines social network analyses with family (twin and sibling) designs to answer these questions via data from the Natio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
109
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 131 publications
(119 citation statements)
references
References 64 publications
9
109
0
1
Order By: Relevance
“…Consistent with other research (e.g., Barnes et al, 2006), adolescent drinking and deviant friends were associated across adolescence. Whereas most studies examine deviant peers as a predictor of alcohol use (Cruz et al, 2012;Duncan et al, 2006;Trucco et al, 2011;van der Vorst et al, 2009), we took a novel approach, examining how these behaviors covaried over time, and found that for most individuals the two were tightly linked. However, these effects were not universal: those low in childhood disinhibition and parental alcohol use were less likely to demonstrate tightly coupled drinking and deviant-friend affiliation across adolescence than same-age peers.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Consistent with other research (e.g., Barnes et al, 2006), adolescent drinking and deviant friends were associated across adolescence. Whereas most studies examine deviant peers as a predictor of alcohol use (Cruz et al, 2012;Duncan et al, 2006;Trucco et al, 2011;van der Vorst et al, 2009), we took a novel approach, examining how these behaviors covaried over time, and found that for most individuals the two were tightly linked. However, these effects were not universal: those low in childhood disinhibition and parental alcohol use were less likely to demonstrate tightly coupled drinking and deviant-friend affiliation across adolescence than same-age peers.…”
Section: Discussionmentioning
confidence: 99%
“…A few studies have considered the infl uence of peer deviance on adolescent alcohol use trajectories, with peer effects measured at either single (Cruz et al, 2012;Feldman et al, 2009;van der Vorst et al, 2009) or co-occurring longitudinal assessments (Martino et al, 2009;Wiesner et al, 2008). For example, one study found that, compared with stable low affi liation with peers who drink, a pattern of steadily increasing affi liation predicted greater likelihood of higher-risk drinking trajectories, and stable high affi liation with drinking peers was strongly associated with stable heavy drinking from age 14 to 19 years (Martino et al, 2009).…”
Section: U Nderage Alcohol Use Is Common In the United Statesmentioning
confidence: 99%
See 1 more Smart Citation
“…12 Medicine and public health have a rich tradition of efforts to change norms and hence move individuals and communities toward better health. 5,13,14 However, a key task of interventions seeking to do this is to identify the valid community or "reference group" for each individual in the population of interest. Normative change hinges on the fact that the individuals involved place a value on the expectations of those with whom they share social connections.…”
mentioning
confidence: 99%
“…Jugendliche mit ähnli-chen genetisch angelegten Temperamentsmerkmalen etwa hinsichtlich des Risikoverhaltens könnten sich sowohl zueinander als auch zu Alkohol oder Drogen hingezogen fühlen (Dick et al 2007;Hill et al 2008). So können der Alkohol-und Drogenmissbrauch von Freunden ebenso aufgrund ihrer genetischen Ähnlichkeiten korreliert sein wie aufgrund ihrer Sozialisationserfahrungen, auch wenn der Gruppendruck der Freunde beim jugendlichen Trinken nicht ausschließlich genetisch bedingt ist (Cruz et al 2012).…”
Section: Alkohol Und Drogenmissbrauchunclassified